DEVELOPING OF â€œBAHASAâ€ INDONESIAN LANGUAGE LECTURE MATERIALS TO INCREASE SKILLS WRITING STUDENTS S-1 NURSING BINA SEHAT PPNI HEALTH SCIENCE INSTITUTE - Moh Zainudin; eka nurjanah; ASEF WILDAN MUNFADLILA (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
language â€œbahasaâ€ teaching materials to improve the writing skill of the S-1 students of Nursing Stikes Bina Sehat Ppni Mojokerto is based on the needs analysis of the S-1 Nursing students. the analysis of the characteristics of the S-1 nursing students, and the need analysis for lecturers. In the requirement analysis for students, the average score obtained by the category strongly agree (SS) for the development of teaching materials got 29.6%, and the category agreed (S) got 62%. Likewise with the analysis of student characteristics, the average score of students who strongly agree (SS) get the number 29.4%. Furthermore, the students who agreed (S) obtained a score of 33.4%. Likewise with the questionnaire needs for lecturers who want a module in the learning process. The purpose of this study is to obtain an objective description of the needs of learning materials and obtain an objective description of the Indonesian language teaching materials development model to improve students writing skill S-1 nursing stikes bina sehat ppni mojokerto. Development of Indonesian Language Material to Improve Student Writing Skill S-1 Nursing Stikes Bina Sehat Ppni Mojokerto, using 4-D development model (four D model). The 4-D development model consists of four development stages: define, design, develop, and disseminate or be adapted into 4-P models (model 4 P), defining, designing, developing, and deploying. Given the limitation of the researcher on financial problems, for the stage of dissemination is not done. The result of analysis of validation sheet of material experts, designers and learning media, and practitioners expert, can be concluded that the teaching material is very valid. It can be known based on the value in the material expert's validation sheet reaching 92.5%. Designer and learning media expert who reached 93%, and expert practitioners who reached 89%. With the explanation that the values entered in the scoring scale are very valid. Keywords: development of teaching materials, modules, writing skills, S-1 Nursing students